An ex vivo approach to understanding sex-specific differences in placental androgen signalling in the presence and absence of inflammation. (24th March 2022) - Meakin, Ashley S.; Gough, Madeline; Saif, Zarqa; Clifton, Vicki L.
Abstract: Introduction: The mechanisms that contribute to continued male intrauterine growth in response to an adverse maternal environment, such as those brought on by maternal asthma, remain largely undefined but may, in part, be mediated by androgen-mediated signalling. We previously reported the expression of multiple AR protein isoforms in the human placenta and proposed the novel AR-45 isoform to be integral in mediating male-specific androgen-dependent signalling in the presence of maternal asthma. In the current study we have used an ex vivo approach to further understand sex-specific differences in placental androgen signalling in the presence and absence of inflammation using human term villous placental explants. Methods: Explants were cultured in the presence and absence of 0.1 nM dihydrotestosterone (DHT), 1 μg/ml lipopolysaccharide (LPS), or DHT + LPS for 24hr. Tissue was used for gene expression and subcellular AR protein isoform expression. Results: Cytoplasmic and nuclear AR protein isoforms expression did not vary between culture conditions in either sex. AR-45 activity was upregulated in male placentae cultured in DHT, LPS and DHT + LPS only. There were no changes in the expression of androgen-mediated downstream targets in males in response to culture conditions, but females had significantly reduced IGF1R expression in response to LPS. Discussion: Increased AR-45 activity in the presence of inflammation may drive continued male feto-placental growth via maintained expression of downstream growth targets. Our findings build on previous work suggesting an important role for AR-45 in regulating male-specific adaptations to placental inflammation and underscores the need to further characterise the function of this AR isoform. Highlights: Total AR expression is enhanced in placental blood vessels Multiple AR protein isoforms are expressed in term villous placental explants In males, nuclear AR-45 expression increased in response to inflammation Reduced IGF1R expression in females in response to inflammation; no change in males AR-45 signalling may retain male feto-placental growth in adverse conditions